EXAM SYSTEM IN NEW SCHOOL STUDENT TARUNA MANDIRI USING PHP MySQL. - RINA ROSMALIA (Jurnal Sistem Informasi, 2009)
Role of Information Technology at the current human activities is so great. Where information technology has become the main facility for business activities, contributed greatly to changes intrinsic to the structure, operations and operations management. In the application of information technology, the most common basis is the need to reduce costs, increase flexibility and response. In the development of education, the application of information technology proved to have advantages over manual systems, including in terms of time and cost efficiency. Activities of new student entrance exam is very important in school activities, and therefore needed a system that can support these activities. To the authors tried to apply a system of entrance examinations of new students according to the needs of users so that users can interact with both.